2016
DOI: 10.1186/s12939-016-0442-5
|View full text |Cite
|
Sign up to set email alerts
|

The gender gap among school children in poor rural areas of western China: evidence from a multi-province dataset

Abstract: BackgroundThe gender gap remains a major impediment in the path towards equality and it is especially wide in low-income countries. Up to the early 2000s, many studies documented extensive inequalities in China: girls had poorer health, less nutrition and less education than their male counterparts. The goal of this study is to examine whether the gender gap persists, given that China is now making the transition into the ranks of upper-middle income countries. We consider educational outcomes, mental and phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Sex differences in smoking are very prominent in Asia, especially in China, where in 2010 the estimated male smoking rate was 22 times as high as that in women (52.9% vs. 2.4%) [28]. Another cruel fact for older Chinese women is that former rural China traditionally valued sons over daughters, so limited educational resources were always allocated to men rather than women in the past [29,30]. In line with these studies, the smoking rate in females and illiteracy rate in males were only 0.4% and 1.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in smoking are very prominent in Asia, especially in China, where in 2010 the estimated male smoking rate was 22 times as high as that in women (52.9% vs. 2.4%) [28]. Another cruel fact for older Chinese women is that former rural China traditionally valued sons over daughters, so limited educational resources were always allocated to men rather than women in the past [29,30]. In line with these studies, the smoking rate in females and illiteracy rate in males were only 0.4% and 1.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety was assessed using the MHT [ 15 ] in this study, the most extensively used scale to measure mental health in China [ 16 , 17 ]. Of the 100 test questions, 10 are reliability questions to detect whether answers were honestly answered.…”
Section: Methodsmentioning
confidence: 99%
“…Although it is beyond the scope of this paper to identify the exact reasons behind the different effects on boys and girls, one possible reason is that these gender disparities already exist in general and that once migration occurs the absence of parents exacerbates the problem. Past research in rural China has shown that in general girls are more susceptible than boys to mental health issues like anxiety (Zhou et al, 2016) and that emotional support from parents may have a stronger impact on the mental well-being of girls than boys (Cross and Madson, 1997;Ma and Huebner, 2008). Thus, the psychological well-being of girls therefore might be more negatively impacted when they lose the emotional support of their parents.…”
Section: Heterogeneous Resultsmentioning
confidence: 99%